2018
DOI: 10.1155/2018/1723695
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Myonecrosis: A Diagnostic and Treatment Challenge in Longstanding Diabetes

Abstract: Objective Diabetes mellitus is associated with microvascular and macrovascular complications; the most commonly recognized ones include diabetic nephropathy, retinopathy, and neuropathy. Less well-known complications are equally important, as timely recognition and treatment are essential to decrease short- and long-term morbidity. Methods Herein, we describe a case of a 41-year-old female with longstanding, uncontrolled type 2 diabetes, who presented with classical findings of diabetic myonecrosis. Results Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Since it is a chronic disease, studies have shown that there is a high recurrence and high mortality rate. The reported recurrence rate is 34.9 to 47.8%, with the contralateral limb affected within six months, and the mortality rate is five years and is associated with the secondary complications of diabetes mellitus [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it is a chronic disease, studies have shown that there is a high recurrence and high mortality rate. The reported recurrence rate is 34.9 to 47.8%, with the contralateral limb affected within six months, and the mortality rate is five years and is associated with the secondary complications of diabetes mellitus [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, DMN is commonly seen in patients with poorly controlled diabetes mellitus, which was evident in our patient in the setting of an HbA1c of 16.7, with acute onset of painful swelling over four weeks prior to presentation to the ED. Commonly affected sites include the anterior thigh, which our patient had, in addition to associated mild swelling and tenderness to the site [ 3 ]. He was found to have laboratory findings of elevation in ESR (>140) and CRP (4.53), with normal CK levels (164) and no obvious leukocytosis as his white blood cell count was 6.9 10^3/uL (4.5 - 11.1 10^3/uL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly affected muscle groups in diabetic myonecrosis are the anterior thigh, calf, and posterior thigh, followed by muscles in the upper extremities. 5 Patients with diabetic myonecrosis have an overall mean age at presentation of 44.6 years; affected patients with type 1 diabetes mellitus present at a mean age nearly 20 years younger than those with type 2 diabetes mellitus (35.9 years vs 52.2 years, respectively). 6 Patients tend to have a long (often >15 years) history of diabetes with microvascular complications such as retinopathy (reported in 71%), nephropathy (reported in 57%), and/or neuropathy (reported in 55%).…”
Section: Discussionmentioning
confidence: 99%
“…Myonecrosis represents an abysmal control of diabetes. Establishing the diagnosis of myonecrosis is firm evidence of how severe the underlying vascular disease has already become, and these patients, independent of the course of myonecrosis, have an increased vulnerability to serious complications of micro- and macrovascular nature [7]. Multiple studies assessing the natural history of patients with diabetic myonecrosis have found that ischemic necrosis is a strong predictor of future cardiovascular morbidity and mortality [1,8].…”
Section: Discussionmentioning
confidence: 99%